Recovery from fast crashes: Role of mutual funds - Ravi Jagannathan; Loriana Pelizzon; Ernst Schaumburg; Mila Getmansky Sherman; Darya Yuferova (Leibniz Institute for Financial Research SAFE, 2021)
We study the role mutual funds play in the recovery from fast intraday crashes based on data from the National Stock Exchange of India for a single large stock. During normal times, trading activity and liquidity provision by mutual funds is negligible compared to other traders at around 4% of overall activity. Nevertheless, for the two intraday marketwide crashes in our sample, price recovery took place only after mutual funds moved in. Market stability may require the presence of well-capitalized standby liquidity providers for recovery from fast crashes.
Keywords: G12; G14; 330; Liquidity Provision; Market Fragility; Flash Crash; Slow-Moving Capital